(untitled) (Journal of Pharmaceutical Negative Results, 2016)
Introduction: Dipyridamole (DIP) might be beneficial in heart failure (HF). Ithas been reported to improve symptoms in observational, small‑scale studies. ThePRoFESS study for secondary prevention of stroke observed a reduction in the riskof HF with acetylsalicylic acid (ASA) plus DIP in comparison with clopidogrel. Thepresent pilot study was aimed at assessing the clinical effects of DIP and ASA in dilatedcardiomyopathy. Materials and Methods: Nineteen outpatients with nonischemicHF, New York Heart Association (NYHA) Class II, ejection fraction (EF) <40%,were randomized to ASA 25 mg, or ASA 25 mg plus DIP 200 mg (ASA + DIP),twice daily. They were evaluated at baseline and after 6 months for symptoms, EF, andexercise capacity through 6‑min walk test. Results: Eleven subjects were in the ASAgroup and 8 in the ASA + DIP. Dyspnea improved, without differences between thetwo arms: n = 6/5/0/0 for NYHA I/II/III/IV in ASA, n = 4/3/1/0 in ASA + DIP. EFincreased in both groups (ASA: from 34 [28–35%] to 40 [32–46%]; ASA + DIP from32.5 [25.75–34%] to 36 [31.5–46%]). No change in meters walked or points in theBorg scale was observed. In a similar population, an adequately powered study wouldneed to recruit 38 subjects. Conclusion: The study, although underpowered, did notshow any difference between the two treatment strategies. While this appears in contrastwith previous studies, the strict inclusion criteria, the randomized, double‑blind design,and the clinical end‑points give strength to our findings. A properly sized trial wouldbe within the capabilities of a single center.